2020
DOI: 10.1001/jama.2020.6173
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Influenza Activity During the SARS-CoV-2 Outbreak in Japan

Abstract: The 2 positive samples showed detection of E and RdRp. Sanger sequencing revealed 100% identity with the SARS-CoV-2 E gene. Only 1 pool showed a positive E signal that was not reproducible with testing of the individual samples of that pool.Discussion | Results from this screening strategy support that the burden of disease in the San Francisco Bay Area early in the pandemic was low; less than 1% of all symptomatic individuals with negative routine testing had SARS-CoV-2 infection. The timing of the positive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
239
2
13

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(300 citation statements)
references
References 4 publications
27
239
2
13
Order By: Relevance
“…This decreases the transmission potential for these diseases by changing the mixing patterns within the host population [ 35 , 80 ]. sd policies motivated by the sars-cov-2 pandemic also reduced the transmission potential of sars-cov-2 as well as other respiratory illnesses [ 81 , 82 ]. A change in human movement patterns can likewise influence the transmission pattern of vector-borne diseases, as evidenced from this study—primarily through changing the host risk of exposure to vectors, but in the opposing direction.…”
Section: Discussionmentioning
confidence: 99%
“…This decreases the transmission potential for these diseases by changing the mixing patterns within the host population [ 35 , 80 ]. sd policies motivated by the sars-cov-2 pandemic also reduced the transmission potential of sars-cov-2 as well as other respiratory illnesses [ 81 , 82 ]. A change in human movement patterns can likewise influence the transmission pattern of vector-borne diseases, as evidenced from this study—primarily through changing the host risk of exposure to vectors, but in the opposing direction.…”
Section: Discussionmentioning
confidence: 99%
“…[25] However, seasonal influenza activity was lower in 2020 than in previous years in Japan. [26] It may have been affected by temperature or virulence and by measures taken to constrain the SARS-CoV-2 outbreak. [26] The coinfection of COVID-19 and influenza A reported in Iran also highlighted the importance of considering SARS-CoV-2 PCR assay regardless of positive findings for other pathogens during the epidemic.…”
Section: Ili Surveillance and Potential Of Novel Eidsmentioning
confidence: 99%
“…[26] It may have been affected by temperature or virulence and by measures taken to constrain the SARS-CoV-2 outbreak. [26] The coinfection of COVID-19 and influenza A reported in Iran also highlighted the importance of considering SARS-CoV-2 PCR assay regardless of positive findings for other pathogens during the epidemic. [27] Silverman et al explored how ILI outpatient surveillance data could be used to estimate the prevalence of COVID-19, and they found a surge in noninfluenza ILI above the seasonal average in March 2020 and showed that this surge correlated with COVID-19 across states.…”
Section: Ili Surveillance and Potential Of Novel Eidsmentioning
confidence: 99%
“…1 A declining trend in influenza following the COVID-19 outbreak has already been indicated in Brazil, Singapore and Japan. [2][3][4] According to the Infectious Diseases Weekly Report Japan, 5 besides influenza, the incidences of Mycoplasma pneumoniae pneumonia, respiratory syncytial virus infection, infectious gastroenteritis, epidemic keratoconjunctivitis and other droplet or contact transmission diseases are also markedly lower than those in the same periods in previous years.…”
mentioning
confidence: 99%